Porous Organic Salts: Diversifying Void Structures and Environments. (19th May 2022) - Ami, Takahiro; Oka, Kouki; Tsuchiya, Keiho; Tohnai, Norimitsu
Abstract: Porous organic salts (POSs) are porous organic materials, in which various aromatic sulfonic acids and amines are regularly self‐assembled by charge‐assisted hydrogen bonding. POSs exhibit high solubility in highly polar solvents. Therefore, they are prepared via facile recrystallization and exhibit high recyclability. In this study, tetrahedral‐structured tetrasulfonic acid and triphenylmethylamine (TPMA) were combined to construct POSs with rigid diamond networks called diamondoid porous organic salts ( d ‐POSs). Furthermore, by introducing substituents (e.g., F, Cl, Br, or I) at the para ‐positions of benzene rings of TPMA, these substituents were exposed on the void surface of d ‐POSs, and their diamond networks were distorted. This induced the formation of a variety of void structures and environments in the d ‐POSs, which significantly affected their gas adsorption behavior. In particular, the d ‐POS from TPMA substituted by fluorine exhibited very high CO2 adsorption of 182 mL(STP) g −1 at 1 atm in all‐organic porous materials. Abstract : Various aromatic sulfonic acids and amines were self‐assembled by charge‐assisted hydrogen bonding to form porous organic salts. This study demonstrates the advantages of diverse porous organic salts, such as all‐organic, extremely facile preparation methods, diverse void structures and environments, and excellent CO2 adsorption properties.